2022
DOI: 10.1039/d1lc00550b
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid skin chips for toxicological evaluation of chemical drugs and cosmetic compounds

Abstract: Hybrid skin models for safety tests of drugs and cosmetics for topical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…As the first line of defense of endogenous antioxidants in the human body, GSH can be regarded as an essential marker indicating OS status and serves as a quantitative toxicological assessment. To illustrate, GSH has been applied in a skin-liver model to quantify the allergic toxicity of topical cosmetics to the liver [166]. Nowadays, several fermentation techniques have solved the common problem of low GSH production yield [167,168].…”
Section: Antioxidant Peptides In the Cosmetic Industrymentioning
confidence: 99%
“…As the first line of defense of endogenous antioxidants in the human body, GSH can be regarded as an essential marker indicating OS status and serves as a quantitative toxicological assessment. To illustrate, GSH has been applied in a skin-liver model to quantify the allergic toxicity of topical cosmetics to the liver [166]. Nowadays, several fermentation techniques have solved the common problem of low GSH production yield [167,168].…”
Section: Antioxidant Peptides In the Cosmetic Industrymentioning
confidence: 99%
“…Légues et al 109 also developed an innovative 3D full-size bioprinted human skin model, which contains immune cells, for screening cosmetic ingredients aimed at reducing or preventing inflammation. Lee et al 110 reported a mixed human skin model capable of performing a detailed toxicological evaluation of drug and cosmetic compounds (Fig. 5c).…”
Section: Toxicological Evaluationmentioning
confidence: 99%
“…Furthermore, lactic acid, used in anti-wrinkle cosmetics, administered simultaneously with strontium chloride suppressed neuronal activation. Interestingly, indicators of hepatotoxicity were detected after topical administration of hepatotoxic compounds at lower levels than in liver cell monolayer cultures, demonstrating the role of the skin barrier [ 67 ]. However, the lack of sensitivity studies in some models, together with the variability of patient samples, limits the model.…”
Section: Biological Requirements For Skin-on-chip (Soc) Devicesmentioning
confidence: 99%